2010
DOI: 10.1002/eji.200939937
|View full text |Cite
|
Sign up to set email alerts
|

Requirements for control of B‐cell lymphoma by NK cells

Abstract: The role of NK cells in the control of endogenously arising tumors is still unclear. We monitored activation and effector functions of NK cells in a c‐myc‐transgenic mouse model of spontaneously arising lymphoma. At early stages, tumors demonstrated reduced MHC class I expression and increased expression of natural killer group 2D ligands (NKG2D‐L). NK cells in these tumors showed an activated phenotype that correlated with the loss of tumor MHC class I. With increasing tumor load however, NK‐cell effector fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
62
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(65 citation statements)
references
References 50 publications
3
62
0
Order By: Relevance
“…The ability of tumor cells to deliver this activation is probably lost during tumor progression, as suggested in the Burkitt's lymphoma Em-myc mouse model. 48 Based on our data, we propose that the first signal delivered by damaged or transformed target cells relates to exosomes that present activating ligands such as BAG6. A failure of exosome stimulation results in NK cell anergy, further driven by soluble inhibitory factors in the microenvironment (see Figure 7).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The ability of tumor cells to deliver this activation is probably lost during tumor progression, as suggested in the Burkitt's lymphoma Em-myc mouse model. 48 Based on our data, we propose that the first signal delivered by damaged or transformed target cells relates to exosomes that present activating ligands such as BAG6. A failure of exosome stimulation results in NK cell anergy, further driven by soluble inhibitory factors in the microenvironment (see Figure 7).…”
Section: Discussionmentioning
confidence: 78%
“…This means that activation of NK cells by extracellular ligands "in trans" is possible, which poses the question of how NK cells may retain their specificity against the damaged (and exosomes releasing) target cells. One possible explanation is that NK cells need a second signal as previously discussed 47,48 that is delivered by direct cell-cell contact. The ability of tumor cells to deliver this activation is probably lost during tumor progression, as suggested in the Burkitt's lymphoma Em-myc mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, our data also show that HTR-8 CM (but not ; however, this effect is compromised by direct cellular interactions, as reported in studies regarding tumor-infiltrating NK cells. 33,37,38 Because the IFN-c signaling blockade can improve the EVT expansion in vitro, 39 the suppressed IFN-c production of dNK cells by soluble trophoblastic factors may create a unique microenvironment to facilitate the further invasion of trophoblast cells. However, the in vivo situation is much more difficult to examine due to existing complex molecular networks and cellular interactions.…”
Section: Discussionmentioning
confidence: 99%
“…In parallel, spleen NK cells from tumor-bearing mice did not show defects in cytotoxicity, whereas IFN-␥ production was reduced in response to PMA/Ionomycin, but not to IL-12 stimulation. Recently, Brenner et al [50] reported that in a transgenic mouse model of spontaneously arising lymphoma, effector functions of tumor-infiltrating NK cells became paralyzed during tumor progression.…”
Section: Nk Cells Within the Tumor Microenvironmentmentioning
confidence: 99%